Anaerobic Bacteremias in Left Ventricular Assist Devices and Advanced Heart Failure - David R. Murillo-Garcia; Julian Galindo; Natalia Pinto; Gabriel Motoa; Esther Benamu; Carlos Franco-Paredes; Daniel B. Chastain; Andrés F. Henao-Martínez (Case Reports in Infectious Diseases)
Left ventricular assisted devices (LVADs) have revolutionized the treatment of advanced heart failure, providing meaningful increases in survival, functional capacity, and quality of life. There are two categories of LVADs patients: (1) bridge-to-transplant and (2) destination therapy. Advanced heart failure and destination LVADs often carry a poor prognosis. The overall 1-year mortality rate remains as high as 30%. LVAD-specific infections, LVAD-related infections, and non-LVAD-related infections represent important emerging clinical problems in this setting. With an incidence ranging from 30 to 50%, these lead to high rates of hospitalization, morbidity, and mortality. Bacteremias caused by anaerobic pathogens in patients with LVAD are underreported. Herein, we describe the microbiological findings, treatment, and clinical outcome of four patients with LVADs and advanced heart failure with anaerobic bacteremias. Fusobacterium species was the most frequent etiological agent. Most patients had a relatively favorable short-term outcome with survival rates of 100% at 30 days and of 50% at 90 days. However, due to other multiple long-term complications, overall mortality remains at 50% during the first year and increases to 75% beyond the first year. Anaerobic bacteremia sources included the oral cavity from odontogenic infections and aspiration pneumonia. Anaerobic bacteremia constitutes an unfavorable mortality prognostic factor in patients with destination LVADs. We recommend implementing preventive strategies with a comprehensive dental care evaluation in patients with LVADs and advanced heart failure.